2005
DOI: 10.1038/sj.eye.6702186
|View full text |Cite
|
Sign up to set email alerts
|

Tear function and goblet cell density after pterygium excision

Abstract: Purpose To evaluate the short-term effect of pterygium excision on tear function and conjunctival goblet cell density. Methods In all, 70 patients (70 eyes) with primary pterygia who underwent a bare-sclera procedure were enrolled in this study. Tear break-up time, Schirmer, and tear-ferning tests and conjunctival goblet cell density obtained by impression cytology were evaluated before and 1 month after surgery. Results At 1 month postoperation, the tear break-up time (11.4973.76 s) was significantly prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…Tear osmolarity, however, deteriorated after 12 months in cases of pterygium recurrence. The authors inferred that pterygium excision improves tear film function, supporting similar findings of two previous studies [23,24], and concluded that pterygium recurrence leads to dry eye.…”
Section: Discussionsupporting
confidence: 82%
“…Tear osmolarity, however, deteriorated after 12 months in cases of pterygium recurrence. The authors inferred that pterygium excision improves tear film function, supporting similar findings of two previous studies [23,24], and concluded that pterygium recurrence leads to dry eye.…”
Section: Discussionsupporting
confidence: 82%
“…But the Schirmer test still showed no significant difference. Li et al [14] have shown similar results. In their study, 70 eyes (70 patients) were enrolled and underwent a bare-sclera procedure.…”
Section: Discussionmentioning
confidence: 56%
“…The results of the MFT showed that the ratio of normal crystallization in the affected eyes was significantly increased 4 and 8 weeks after the operation, which coincided with BUT. We could conclude from our results that once formed, pterygium itself leads to abnormal tear film function [14] . Pterygium excision combined with limbalconjunctival autograft transplantation can partially restore the tear functions into normal state in the affected eyes.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Finally, it develops a vicious circle in which the tear hyperosmolarity same stimulates the expression of MMP and leads to inflammation of the ocular surface [71]. A study shows that excision of pterygium improves the osmolarity and function of the tear film, bringing an improvement of the tear BUT and ferning tests, due to increase in density of conjunctival GCs and lacrimal mucous component [72]. However, the tear osmolarity remains stable for the time in which no pterygium recurrence.…”
Section: Pterygiummentioning
confidence: 99%